Chemistry : An atoms-focused approach - Gilbert, Thomas R; Kirss, Rein V; Foster, Natalie (Canada : Norton., 2014)
The authors, who have more than two decades of combined experience teaching an atoms-first course, have gone beyond reorganizing the topics. They emphasize the particulate nature of matter throughout the book in the text, art, and problems, while placing the chemistry in a biological, environmental, or geological context. The authors use a consistent problem-solving model and provide students with ample opportunities to practice.
Appendix APP-1-33p.; Glossary G-1-13p.; Index I-1-28p.
Keywords: Electrochemistry; Nuclear chemistry; Thermodynamics; Matter and energy